Genome wide comparative analysis of the effects of PRMT5 and PRMT4/CARM1 arginine methyltransferases on the Arabidopsis thaliana transcriptome - Hernando, Carlos Esteban (2015)
BACKGROUND: Methylation at arginine residues (R) is an important post-translational modification that regulates a myriad of essential cellular processes in eukaryotes, such as transcriptional regulation, RNA processing, signal transduction and DNA repair. Arginine methylation is catalyzed by a family of enzymes known as protein arginine methyltransferases (PRMTs). PRMTs are classified as Type I or Type II, depending on the position of the methyl group on the guanidine of the methylated arginine. Previous reports have linked symmetric R methylation to transcriptional repression, while asymmetric R methylation is generally associated with transcriptional activation. However, global studies supporting this conclusion are not available. RESULTS: Here we compared side by side the physiological and molecular roles of the best characterized plant PRMTs, the Type II PRMT5 and the Type I PRMT4, also known as CARM1 in mammals. We found that prmt5 and prmt4a;4b mutants showed similar alterations in flowering time, photomorphogenic responses and salt stress tolerance, while only prmt5 mutants exhibited alterations in circadian rhythms. An RNA-seq analysis revealed that expression and splicing of many differentially regulated genes was similarly enhanced or repressed by PRMT5 and PRMT4s. Furthermore, PRMT5 and PRMT4s co-regulated the expression and splicing of key regulatory genes associated with transcription, RNA processing, responses to light, flowering, and abiotic stress tolerance, being candidates to mediate the physiological alterations observed in the mutants. CONCLUSIONS: Our global analysis indicates that two of the most important Type I and Type II arginine methyltransferases, PRTM4 and PRMT5, have mostly overlapping as well as specific, but not opposite, roles in the global regulation of gene expression in plants.